Quality Evaluation and Causal Analysis of Crude Palm Oil Based on Critical Quality Parameters: Free Fatty Acids, Moisture, and Impurities - Jaya, Jaka Darma; Khairiah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2025)
Crude Palm Oil (CPO) is a vital commodity derived from the processing of sterilized oil palm mesocarp extracted from Fresh Fruit Bunches (FFB), serving as a primary raw material in the edible oil industry. The quality of CPO is critically influenced by parameters such as Free Fatty Acid (FFA), moisture content, and impurities, which directly affect its stability, shelf life, and market value. Despite established quality standards, many CPO production facilities continue to face inconsistencies in these parameters due to variations in harvesting practices, post-harvest handling, and processing conditions, yet few studies have explored plant-specific root causes. This study aimed to evaluate the quality of CPO at XYZ Co. in Barito Kuala Regency by analyzing FFA levels, moisture content, and impurity content through a qualitative-descriptive approach, including field observations, staff interviews, and analysis using bar charts and fishbone diagrams, with data collected from October 2023 to January 2024. Results showed that FFA levels remained within the company's standard of 5%, ranging from 3.9% to 4.06%; moisture content varied between 0.25% and 0.35%, with some values exceeding the limit; while impurity levels surpassed the 0.030% threshold in two observation periods. Fishbone diagram analysis identified human error, substandard raw materials, poor machine maintenance, and non-compliance with standard operating procedures as key contributing factors. The study recommends improvements in supervision, operator training, equipment maintenance, and SOP implementation to enhance and maintain consistent CPO quality